The Characteristics and Prognosis of Relapsed Patients with Pulmonary Tuberculosis - Trini Suryowati; Randolph Serep Marantuan; Putri Manuella Ussy Taneo (GLOBAL HEALTH SCIENCE GROUP, 2025)
Relapsed Pulmonary Tuberculosis is a condition of patients infected with Mycobacterium tuberculosis who have received complete OAT treatment and are declared cured but are re-infected. Based on WHO (World Health Organization) data in 2014, there were 7,840 cases of relapsed pulmonary tuberculosis in Indonesia. This study aims to determine the characteristics and prognosis of relapsed pulmonary tuberculosis patients at the Kramat Jati District Health Centre for the 2021-2022 period. This study uses medical record data with a retrospective descriptive method. In this study, data results were obtained on patients with Relapse Pulmonary Tuberculosis who were treated at the Kramat Jati District Health Center in the period 2021-2022, as many as 34 patients whose criteria met the inclusion criteria. The data obtained were data in the form of age, gender, type of pulmonary tuberculosis diagnosis, occupation or status, previous treatment history, anti-tuberculin drug guidelines, prognosis, which can be used as variables in this study. The data analysis used in this study is using descriptive statistical data methods with frequency analysis. The results showed that patients aged 21-40 years were (32.4%). Male gender (67.6%), bacteriological confirmed diagnosis type (94.1%). Type of employment or other status (58.8%), previous treatment history of relapse patients (61.8%), category 2 OAT guideline patients (82.4%). The prognosis of relapsed pulmonary tuberculosis patients tended to be good (27%). This study concludes that the prognosis of relapsed pulmonary tuberculosis patients with complete treatment category 2 tends to be good.